The role of educational management in expand of social security - Dana Lateef Shwani; Yousif Maghdid Qader; Karzan Qader Hamad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Abstract The importance of the social security for all the society is very high, Also the channels that are responsible for the social security are all multiplied from the society to another society, the channels that are changing, as well as those societies that have the right idea for the authority, we see that the social, educational, cultural and economic crisis of the society will be decreasing. It is evident that every effort to expand and deepen social security in society must pay attention to education and educational institutions so that society can continue in a state of social security. In this regard, we come to the conclusion that social responsibility and the provision of appropriate education and mental health for individuals play a major role in expanding social security, in addition to the influence of the family in ensuring social security in society. On the other hand, it can be said that all social institutions can play a role in expanding the scope of social security, and the social order and organization that is the basis of educational institutions can become the expansion of social security. Our main goal is to try to analyze the effects of educational management in expanding social security, because we ultimately conclude that education plays a major role in expanding and developing social security.